Diagnosis of Non-alcoholic Fatty Liver Disease (NAFLD): Current Concepts - Papatheodoridi, Margarita; Cholongitas, Evangelos (Current Pharmaceutical Design, 2018)
Nonalcoholic fatty liver disease (NAFLD) ranges from simple hepatic steatosis to non-alcoholic steatohepatitis (NASH) and cirrhosis. The majority of NAFLD patients do not progress to NASH and their morbidity risk is low. However, clinical and economic burden of the disease is considerable since the prevalence of the disease is estimated as high as 25% of the general population. Liver biopsy remains the current gold standard for diagnosis, despite limitations regarding sampling variability, invasive nature, and high cost. However, numerous non-invasive biomarkers, including mainly serum markers or imaging modalities, intend to detect the presence of steatosis, NASH or advanced fibrosis. To date, ultrasound is suggested as first-line screening tool for defining steatosis in a selected population, while diagnosis of NAFLD requires exclusion of other chronic liver disease etiology or other steatosis causes. A crucial step in the management of NAFLD patients is the identification of advanced fibrosis, which may be reliably excluded by using NAFLD-Fibrosis score or FIB-4 score or by performing transient elastography. The most robust modalities implement Magnetic Resonance technology and manage to accurately quantify steatosis or identify fibrosis stage, but are not yet applicable in routine practice. The most challenging endpoint has proved to be a non-invasive diagnosis of NASH since no reliable biomarkers have been found to detect or predict inflammation in NAFLD. Lately, research focuses on validating existing markers as robust diagnostic tools for clinical use and investigating novel experimental markers of disease. Current strategies concepts aim to safely diagnose NAFLD patients, aid drug development and finally, guide personalised treatment.
Keywords: fibrosis